Further evidence of alerted default network connectivity and association with theory of mind ability in schizophrenia - GILL, MICHAEL; DONOHOE, GARY; CORVIN, AIDEN; MORRIS, DEREK; FRODL, THOMAS (My University, 2016)
Background: Resting-state functional magnetic resonance imaging (rs-fMRI) has repeatedly shown evidence of altered functional connectivity of large-scale networks in schizophrenia. The relationship between these connectivity changes and behaviour (e.g. symptoms, neuropsychological performance) remains unclear. Methods: Functional connectivity in 27 patients with schizophrenia or schizoaffective disorder, and 25 age and gender matched healthy controls was examined using rs-fMRI. Based on seed regions from previous studies, we examined functional connectivity of the default, cognitive control, affective and attention networks. Effects of symptom severity and theory of mind performance on functional connectivity were also examined. Results: Patients showed increased connectivity between key nodes of the default network including the precuneus and medial prefrontal cortex compared to controls (p < 0.01, FWE-corrected). Increasing positive symptoms and increasing theory of mind performance were both associated with altered connectivity of default regions within the patient group (p < 0.01, FWE-corrected). Discussion: This study confirms previous findings of default hyper-connectivity in schizophrenia spectrum patients and reveals an association between altered default connectivity and positive symptom severity. As a novel find, this study also shows that default connectivity is correlated to and predictive of theory of mind performance. Extending these findings by examining the effects of emerging social cognition treatments on both default connectivity and theory of mind performance is now an important goal for research.
PUBLISHED
Export Date: 27 January 2017 Article in Press
Keywords: Default network; FMRI; Schizophrenia; Social cognition; Default network; FMRI; Schizophrenia; Social cognition